2009
DOI: 10.1007/s00359-009-0444-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification, release and olfactory detection of bile salts in the intestinal fluid of the Senegalese sole (Solea senegalensis)

Abstract: Olfactory sensitivity to bile salts is wide-spread in teleosts; however, which bile salts are released in suYcient quantities to be detected is unclear. The current study identiWed bile salts in the intestinal and bile Xuids of Solea senegalensis by mass spectrometry-liquid chromatography and assessed their olfactory potency by the electro-olfactogram. The main bile salts identiWed in the bile were taurocholic acid (342 mM) and taurolithocholic acid (271 mM) plus a third, unidentiWed, bile salt of 532.3 Da. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 27 publications
0
37
0
Order By: Relevance
“…A similar structural change also occurred in male eel bile, with the immature forms having a series of large peaks A, B, D, F and the adult forms having a lower proportion of A and B, the loss of D and F, and a pair of large new peaks C and E. Goldfish bile is characterized by a single large peak C. Although goldfish and the mature eel bile shared a superficial resemblance based on bile alcohol molecular mass, the identities of their pentahydroxy C 27 bile alcohol sulphates were quite different. Tilapia bile was different from all of the above mentioned forms in having a single large peak H. Bile of the three marine species (seabream, sole and flounder) contained mainly C 24 bile acids taurochenodeoxycholic acid and taurocholic acid (Velez et al, 2009) (data not shown).…”
Section: Bile Compositionmentioning
confidence: 94%
See 2 more Smart Citations
“…A similar structural change also occurred in male eel bile, with the immature forms having a series of large peaks A, B, D, F and the adult forms having a lower proportion of A and B, the loss of D and F, and a pair of large new peaks C and E. Goldfish bile is characterized by a single large peak C. Although goldfish and the mature eel bile shared a superficial resemblance based on bile alcohol molecular mass, the identities of their pentahydroxy C 27 bile alcohol sulphates were quite different. Tilapia bile was different from all of the above mentioned forms in having a single large peak H. Bile of the three marine species (seabream, sole and flounder) contained mainly C 24 bile acids taurochenodeoxycholic acid and taurocholic acid (Velez et al, 2009) (data not shown).…”
Section: Bile Compositionmentioning
confidence: 94%
“…To address this question, the routes and rates of release of olfactory-potent bile compounds needs to be investigated in each species as well as to establish whether males and females release different odorants. There does not always seem to be a perfect match between those bile salts released by a given species and their olfactory potency (Velez et al, 2009;Zhang et al, 2001). The different bile composition between males and females could be related to their different diets.…”
Section: Putative Biological Roles Of Olfactory Sensitivity To Bile Amentioning
confidence: 99%
See 1 more Smart Citation
“…The hormone, 17, 20ß-P or maturation inducing steroid (MIS) was also found to induce maturation in a marine flatfish species, plaice (Pleuronectes platessa), which accumulated MIS in urine indicating that the species may use urine as a vehicle to release steroid pheromones that were synthesized by the gonads (Canario and Scott, 1989). Actually a wide range of substances have been suggested (but few have been demonstrated) as reproductive pheromones that are excreted by fish to the environment such as bile salts Zhang et al, 2001;Li et al, 2002;Huertas et al, 2007), steroid molecules (Barata et al, 2008) and prostaglandins (Velez et al, 2009;Hubbard, 2014) which might be released with different fluids (urine, faeces, mucus) acting as messengers to conspecifics.…”
Section: Chemical Communication Olfaction and Physiologymentioning
confidence: 99%
“…Food-related odorants such as, L-phenylalanine and 1-Methyl-L-tryptophan gave significantly higher electro-olfactogram (EOG) responses in the lower olfactory epithelium (Velez et al, 2007b;Velez et al, 2011) in comparison to the upper olfactory epithelium which in turn had significantly higher EOG responses to conspecific-derived odorants such as taurocholic acid (Velez et al, 2007a;Velez et al, 2009). For this reason, evaluated the different products excreted by Senegalese sole to examine the olfactory sensitivity of those products using EOG between conspecific in the upper olfactory rosette.…”
Section: Chemical Communication Olfaction and Physiologymentioning
confidence: 99%